Male rape in context: measures of intolerance and support for male rape myths (MRMs) - DeJong, Christina (Criminal justice studies, 2020)
Research on myths about male rape victims and offenders indicates that men and heterosexual individuals tend to believe myths about male rape (MRMs), as do individuals with negative attitudes toward gay men. Many who support male rape myths assume that both male victims of rape and offenders are usually gay, or that straight men cannot be raped. Studies on MRM have portrayed male rape in an ‘everyday life’ context, but myths about male rape are likely shaped by its portrayal in film, television and popular culture. For example, respondents may attribute more blame to victims who are incarcerated as opposed to a victim raped by a stranger near their home. In this study, we assess support for myths about male rape victims and whether the context of the situation and various indicators of intolerance play a role in their beliefs. Specifically, we present four fictional scenarios of male rape to respondents: prison, in the military, during a conflict situation, and on a college campus. We find that respondents are less likely to support MRMs in the context of the military, and that race and gender also explain support for MRMs. Measures of intolerance are positively related to support for MRMs, with sexism having the strongest relationship with support.